2022
DOI: 10.3390/su14042082
|View full text |Cite
|
Sign up to set email alerts
|

Characterization and Life Cycle Exergo-Environmental Analysis of Wood Pellet Biofuel Produced in Khyber Pakhtunkhwa, Pakistan

Abstract: Major objectives of this study were to produce low-emitting wood pellet biofuel from selected agro-forest tree species, i.e., Kikar (Acacia nilotica), Oak (Quercus semicarpifolia), and Mesquite (Prosopis juliflora), grown in the southern part of the Khyber Pakhtunkhwa (KP) province of Pakistan using indigenously developed technology (pelletizer machine). Primary raw material, such as sawdust of the selected agro-forest tree species, was obtained from sawmills located in southern part of KP. Life cycle inventor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1

Relationship

3
3

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 41 publications
1
5
0
Order By: Relevance
“…Though the benefits of pellets outweigh that of LPG, the life cycle of pellet production causes severe environmental issues like increased air pollution and intense land changes [ 188 ]. However, the evaluation of pellet production cost considers only internal costs of materials, labor, energy and equipment and leaves environmental externalities to be borne by third parties in the form of medical expenses, accident compensation and poor environmental quality [ 232 ]. The GoG and the Ghana environmental protection agency must ensure that environmental impact assessments of pellet projects are carried out per the environmental statutes of Ghana [ 233 ].…”
Section: Resultsmentioning
confidence: 99%
“…Though the benefits of pellets outweigh that of LPG, the life cycle of pellet production causes severe environmental issues like increased air pollution and intense land changes [ 188 ]. However, the evaluation of pellet production cost considers only internal costs of materials, labor, energy and equipment and leaves environmental externalities to be borne by third parties in the form of medical expenses, accident compensation and poor environmental quality [ 232 ]. The GoG and the Ghana environmental protection agency must ensure that environmental impact assessments of pellet projects are carried out per the environmental statutes of Ghana [ 233 ].…”
Section: Resultsmentioning
confidence: 99%
“…Our results are in accordance with Refs. [13][14][15], which analyzed the environmental impacts of the marble production chain using LCA; their results revealed that electricity and fossil fuels are responsible for the GWP impact category [21,[32][33][34]. As there is no LCA of the marble production chain in Pakistan, we compared our results with other allied LCA-based studies; however, this is one of the limitations and weaknesses of the present study.…”
Section: Resultsmentioning
confidence: 99%
“…As there are no wastewater treatment plant facilities in the marble manufacturing units, as a result, the pollution level increases very quickly in water and soil, and consequently, adversely affects the biotic and abiotic components of the environment [7,20]. Environmental deterioration is not only severely affecting flora and fauna, but it can also affect human beings adversely; therefore, an environmental sustainability assessment of the marble tile production chain is imperative to assess and monitor the pollution level in the air, soil, and water from the marble tile production chain [6]; thus, to calculate its environmental impacts, water footprints, and cumulative energy demand, life cycle assessment (LCA) is applied, which is a recognized tool globally to assess the environmental sustainability of a product or process [21][22][23][24]. LCA estimates and assesses top-ten USA EPA most wanted environmental impacts such as global warming potential, acidification potential, eutrophication potential, abiotic depletion, terrestrial ecotoxicity, marine aquatic ecotoxicity, human toxicity, freshwater aquatic eco-toxicity, ozone layer depletion, and photochemical oxidation of a product across its life cycle stages [23][24][25][26].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…One of the most common methodologies for assessing the environmental impacts of products is life cycle assessment (LCA) [20,[25][26][27]. LCA is a method for examining a product's or process's environmental impact from inception through its final disposal.…”
Section: Introductionmentioning
confidence: 99%